Performance Appraisal, Job Satisfaction and Organizational Commitment in Nepalese Commercial Banks - Aryal, Narayan Prasad; Hamal, Janga Bahadur; Bhatta, Nirjana (Marsyangdi Journal, 2022)
The purpose of this paper is to examine the impact of performance appraisal and job satisfaction on employee organizational commitment in Nepalese commercial banks. The primary data has been used to assess the opinions of the respondents through structured questionnaires constituting Likert items. The survey is based on 172 respondents, which represents 78 percent response of the total efforts made to collect samples from 16 commercial banks of Nepal. Descriptive and causal research designs have been employed in this study. The Pearson correlation coefficient has been used to analyze the relationship whereas the multiple linear regression models have been used for examining the significance and impacts of performance appraisal and job satisfaction on employee organizational commitment in the commercial banks of Nepal. The result reveals that performance appraisal and job satisfaction are positively related to employee organizational commitment. The study, therefore, concludes that job satisfaction and performance appraisal are the important factors affecting employees’ organizational commitment. As this study is confined to commercial banks only, future studies can consider other banking institutions, and among employees‟ profile and human resource management factors as well.